ANALYZING HYBRID WARFARE STRATEGIES ON THE TWITTERSPHERE IN THE CONTEXT OF PAKISTAN - Taj Muhammad; Dr. Zubair Shafiq (International Journal of Contemporary Issues in Social Sciences, 2024)
Nowadays, millions of people share their views on social networking sites, and a large amount of data is generated daily, especially on Twitter. Pakistan's geographical position and geopolitical importance have made it vulnerable to various hybrid threats. Pakistan's enemies, mainly India, have launched a series of hybrid wars using digital media platforms and have polarized the society, hence creating an environment of instability and insecurity. This research paper examines the role of Twitter in facilitating hybrid warfare strategies in the context of Pakistan, highlighting how hybrid warfare unfolds on this platform and presents significant threats to Pakistan's national security. This study identifies and analyzes the patterns of disinformation campaigns through sentiment and network analysis of pro-Pakistan and anti-Pakistan hashtags while exploring the factors contributing to disseminating propaganda narratives. The sentiment of the Twitter dataset was initially classified manually by three independent overseers to reduce the biases. Additionally, machine-learning algorithms were developed to categorize and validate the accuracy of the sentiments of the Twitter dataset as pro-Pakistan, anti-Pakistan, and neutral. The researcher also constructed networks to analyze the community's responses to pro-Pakistan and anti-Pakistan hashtags. Furthermore, this research paper utilized a mixed-methods approach that combines quantitative analysis of Twitter data with qualitative information gathered through reflexive thematic analysis of hybrid warfare experts' interviews.